Physical, physiological and psychological profiles of elite Turkish taekwondo athletes - Khayyat Hadi Nabizadeh; Sağır Sibel Güler; Hataş Özkan; Smolarczyk Marcin; Akalan Cengiz (Sciendo, 2020)
Study aim: To identify the physical, physiological and psychological profiles of elite Turkish taekwondo athletes.